Characteristics of Anterior Segment in Congenital Ectopia Lentis: An SS-OCT Study. (6th June 2022) - Qi, Haotian; Jin, Guangming; Zou, Minjie; Young, Charlotte; Liu, Liyan; Lian, Zhangkai; Guo, Dongwei; Liu, Zhenzhen; Zheng, Danying
Abstract : Purpose . To investigate the characteristics of anterior chamber angle parameters in congenital ectopia lentis (CEL) patients and to evaluate the sensitivity and specificity of anterior segment parameters in distinguishing CEL from healthy controls. Setting . Zhongshan Ophthalmic Center, Guangzhou, China. Design . Cross-sectional study. Methods . 35 CEL patients and 35 age- and sex-matched healthy controls were recruited. Axial length (AL) and anterior segment parameters including anterior chamber width (ACW), angle open distance (AOD), angle recess area (ARA), trabecular-iris space area (TISA), and trabecular-iris angle (TIA) were measured. All the above parameters and the ratio index of angle parameters, which was defined as the angle parameter value of the narrower side to that of the contralateral side, were compared between CEL and controls. Receiver operating characteristic (ROC) curves were also plotted to evaluate the diagnostic performance of anterior chamber angle parameters in CEL patients. Results . All angle parameters of the contralateral side to the dislocated lens side were significantly smaller than those of the dislocated lens side in CEL (all P < 0.05 ). For the diagnostic performance of anterior chamber angle parameters, the ratio index of TIAr500 combined with TIAr750 had the best diagnostic performance for CEL screening (AUC = 0.798), and TIAr500 of 0.887 and TIAr750 of 0.917 were detected to be the optimal cut-off points, representing a sensitivity of 89.8% and specificity of 68.7%. Conclusion . The contralateral side to the dislocated lens side in the CEL had a narrower anterior chamber angle. TIAr500 combined with TIAr750 is the optimal combination strategy for ectopia lentis screening.